2018
DOI: 10.15452/cejnm.2018.09.0028
|View full text |Cite
|
Sign up to set email alerts
|

Effective communication and sharing information at clinical handovers

Abstract: Aim: The aim of this study was to present an overview of current knowledge of approaches to improving patient safety and to ensuring continuity of care at clinical information handovers (handoffs). Design: Descriptive summarizing study. Methods: PubMed, Science Direct, Embase and Google Scholar databases were studied, focusing on papers published in English over the past five years. The overview included papers dealing with the effectiveness of patient information transfer between members of staff, teams, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 31 publications
0
2
0
2
Order By: Relevance
“…Mais pertinente se torna a questão da fluidez entre contextos quando verificamos que a forma de comunicação inter-serviços mais utilizada foi o contacto direto e informal entre os seus profissionais, o revela alguma fragilidade do sistema formal de registo de dados no que concerne à transmissão atempada, completa e inteligível da informação clínica necessária para garantir a continuidade de cuidados. Por outras palavras, é necessário assumir que a comunicação direta entre serviços deve ser formalizada como complemento da utilização dos sistemas de informação instituídos, de forma a garantir a disponibilização eficaz e efetiva de toda a informação necessária (8) .…”
Section: Resultsunclassified
“…Mais pertinente se torna a questão da fluidez entre contextos quando verificamos que a forma de comunicação inter-serviços mais utilizada foi o contacto direto e informal entre os seus profissionais, o revela alguma fragilidade do sistema formal de registo de dados no que concerne à transmissão atempada, completa e inteligível da informação clínica necessária para garantir a continuidade de cuidados. Por outras palavras, é necessário assumir que a comunicação direta entre serviços deve ser formalizada como complemento da utilização dos sistemas de informação instituídos, de forma a garantir a disponibilização eficaz e efetiva de toda a informação necessária (8) .…”
Section: Resultsunclassified
“…In the United States, annually, nursing hand-off communication occurs nearly 300 million times (Eggins & Slade, 2015). Patient clinical hand-off encompasses transferring patient information and care that can be achieved via effective communication (Pokojová & Bártlová, 2018). A study from an oncology center indicated that 60% of medication errors were related to ineffective hand-off communication (Pandya et al, 2019).…”
Section: Possible Solutions For Communicationmentioning
confidence: 99%
“…Sangat disarankan agar moda komunikasi SBAR ini diperluas ke pelayanan kesehatan, khususnya di rumah sakit. Untuk meningkatkan keselamatan pasien, ini dapat mengurangi jumlah insiden yang tidak terduga, seperti cedera atau trauma lainnya, pada pasien yang berisiko jatuhf (Pokojová & Bártlová, 2018). F Dalam konteks upaya perawat untuk mengurangi kesalahan komunikasi dengan menggunakan pendekatan komunikasi efektif SBAR selama proses penimbangan dan penerimaan, penelitian tentang jenis intervensi menghasilkan sebanyak 15 publikasi.…”
Section: Pembahasanunclassified